Determination of pore network accessibility in hierarchical porous solids - Rigby, Sean P.; Hasan, Muayad; Stevens, Lee; Williams, Huw E.L.; Fletcher, Robin S. (American Chemical Society, 2017)
This paper validates the hypothesis that the supposedly non-specific adsorbates nitrogen and argon wet heavy metals differently, and shows how this unexpected effect can be actively utilised to deliver information on pore inter-connectivity. To explore surface chemistry influences on differential adsorbate wetting, new findings for a mixed silica-alumina material were compared with data for pure silica and alumina materials. The new structural characterisation described can determine the distribution of the particular sub-set of meso-and micro-pores that connect directly to macropores that entrap mercury following porosimetry, as mapped by computerised X-ray tomography. Hence, it elucidates the spatial organization of the network and measures the improved accessibility to smaller pores provided by larger pores. It was shown that the silica-alumina pellets have a hierarchical pore-size arrangement, similar to the optimal blood vessel network architecture in animals. The network architecture derived from the new method has been independently validated using complementary gas sorption scanning curves, integrated mercury porosimetry, and NMR cryoporometry. It has also been shown that, rather than hindering interpretation of characterisation data, emergent effects for networks associated with these techniques can be marshalled to enable detailed assessment of the pore structures of complex, disordered solids.